Settlement-type tools from the flint workshop / mine in Bębło, site 4, Wielka Wieś commune - Trela-Kieferling, Elżbieta (Acta Archaeologica Lodziensia, 2018)
In the literature Site 4 at Bęblo is defined as a workshop or a mine. Analysis of recovered artefacts has shown, however, that the assemblage includes a large number of tools related to dwellings, which is untypical of workshop sites or mines. Nearly 400 dwelling-related tools recovered from Site 4 in Bębło by Albin Jura include all types characteristic of the Lengyel-Polgár cycle. The absence of items with sickle gloss may be due to the fact that the settlement area was functionally diversified. It is important to identify the functional zones of the hitherto unknown settlement and to determine the kind of settlement activity at the site.